(untitled) (Research, Society and Development, 2021)
Introduction: Professionals have several problems related to ethics in the work environment, therefore, a positive ethical climate can promote job satisfaction and social well-being of professionals, aiming to identify in scientific productions the factors associated with ethical climate in the hospital environment. Method: Integrative review based on the research question “What are the factors associated with the ethical climate in a hospital?” The search was carried out in the database Web Of Science, SAGE Journals Online and Nursing and Allied Health Literature, 399 articles were found and 12 were selected for analysis. Results: The ethical climate was associated with factors related to work, such as job satisfaction; rotation intent; organizational commitment; moral suffering; leadership; moral courage; professional competence; support and organizational behavior Discussion: The findings showed that there are significant and positive results in relation to the ethical climate and associated factors identified in this study. Thus, presenting positive results, there will be greater compatibility for the ethical climate to be desirable in the work environment. Conclusion: This study shows that there is a predominance of association between ethical climate and job satisfaction, intent to turnover, and organizational commitment. Emphasis is placed on the need for organizational strategies to provide an adequate work ethic in order to guarantee the predominance of care. In addition, it is of paramount importance to provide educational efforts such as ethics guidance and training programs to ensure a mastery of principles.